Perkembangan Kelekatan pada Anak: Perspektif Psikologi dan Islam dalam Menciptakan Gaya Pengasuhan Terbaik di Masyarakat - Rahmatullah, Azam Syukur; Syafii, Muhammad Hisyam (Lembaga Yasin AlSys, 2025)
The aim of this study was to examine how children develop attachment from an Islamic and psychological point of view, and to determine how these two perspectives can work together to create the best parenting style. While insecure attachment can lead to psychological and social problems later in life, secure attachment in parenting is essential in shaping a child's personality, morals, and emotional stability. The research method used is qualitative with a comparative approach to the situation in society related to children and literature studies. The primary sources used are interviews and primary sources through information in interpretations, journals, newspapers and similar researches. The data analysis method used is content analysis with a constant method comparative approach to analyze the similarities and differences between Islamic parenting theories based on the Qur'an, and contemporary attachment theory ideas as proposed by John Bowlby and Mary Ainsworth. The results were obtained that children's spiritual character is formed by attachment, which also has an impact on their psychological health. According to the theory of psychological attachment, a child's social and emotional development is based on a close emotional bond with his or her primary caregiver. In contrast, the Islamic viewpoint places a strong emphasis on moral education, loving upbringing, and a transcendental relationship with Allah SWT. Combining these two methods provides a comprehensive framework to help children develop healthy attachments focused on their psychological health as well as the development of strong moral and spiritual principles. Therefore, the community must try their best in educating children by paying attention to all kinds of their needs as the people in Central Java and West Java do.